Isolated Au Atom Anchored on Porous Boron Nitride as a Promising Electrocatalyst for Oxygen Reduction Reaction (ORR): A DFT Study - Li, Qiaoling; Zhang, Tianran; Yu, Xiaofei; Wu, Xiaoyu; Zhang, Xinghua; Lu, Zunming; Yang, Xiaojing; Huang, Yang; Li, Lanlan (Frontiers in Chemistry, 2019)
The development of efficient, stable, and low-cost catalytic material for the oxygen reduction reaction (ORR) is currently highly desirable but challenging. In this work, based on first-principles calculation, the stabilities, catalytic activities and catalytic mechanisms of isolated Au atom supported on defective porous BN (p-BN) have been studied in detail. The results reveal that the defective p-BN anchor Au atom strongly to ensure the stability of Au/p-BN. Based on frontier molecular orbital and charge-density analysis, isolated Au atom supported on porous BN with VN defect (Au/p-BN-VN) is an effective ORR catalyst. Especially, the low barriers of the formation (0.38 eV) and dissociation (0.31 eV) of *OOH and the instability of H2O2 on Au/p-BN-VN catalyst suggest that ORR proceeds via 4-electron pathway. Along the favorable pathway, the reduction of O2 to *OOH is the rate-limiting step with the largest activation barrier of 0.38 eV and the maximum free energy change is 1.88 eV. Our results provide a useful guidance for the design and fabrication of new Au-base catalyst with high-efficiency and are beneficial for the developing of novel isolated metal atom catalysts for ORR.